PENGATURAN HUKUM INTERNASIONAL TENTANG TANGGUNGJAWAB NEGARA DALAM PENCEMARAN UDARA LINTAS BATAS - Dina S.T Manurung; Suhaidi Suhaidi; Jelly Leviza (Journal of USU International Law, 2014)
ABSTRACT Frequent environmental damage, environmental damage is not a problem to be a novelty in the worl of international. Particularly deforestation occurred in Riau consequently perceived by people around the forest and surrounding communities  Sumatra and also covers aspects of the country off limits resulting in losses for communities neighboring Indonesian citizens. Forest fires in Indonesian has resulted in air pollution in some countries, Malaysia and Singapore in particular countries. Smog problem of forest fires in Riau has become an international issue because the case raises pollution in neighboring Malaysia and Singapore to protest against Indonesian over the cross-border isssues. In the completion of this environmental problem first needs to know which is the principle of state responsibility under international law to make it easier to understand, and need to know what are the settings associated with smoga pollution in the sphere of internationall environmental law. If both are known, it will be easier to know what kind of responsibility do Indonesia associated with smog that cuts across disturbing neighboring. Therefore, legal research methods applied in writing is to use normative research is research that perform searches against the legal norms contained in the applicable rules of dispute resolution such as charter United Nations, Geneva Conventions and Declarations Stockholm and other sources as well obtain materials with library research. The ultimately resulted in the writing of some the conclutions that transboundary air pollution problems can be solved by means of peace, without having to bring to the International Court of Justice as well as fixed priority no party weighed no party, either party to the state that suffered environmental damage, as well as countries that felt the impact of the environmental damage. Because of the environmental issues become issues that must be dealt with together, with respect to international cooperation in the field of international environmental move. Keywords : International Law, State Responsibility, Transboundary Haze Pollution